2022
DOI: 10.1037/ser0000567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a community-based training program for evidence-based treatments for PTSD using the RE-AIM framework.

Abstract: Community mental health providers increasingly serve veterans with posttraumatic stress disorder (PTSD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…To date, community-based providers have been an understudied population in the implementation science literature even though they regularly provide care to those with PTSD. Better understanding barriers to delivering EBPs in routine care is of considerable importance, given evidence suggesting CPT implementation in community settings is lower than those found in VA settings (Dondanville et al, 2021a ; Finley et al, 2018 ; Hundt et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, community-based providers have been an understudied population in the implementation science literature even though they regularly provide care to those with PTSD. Better understanding barriers to delivering EBPs in routine care is of considerable importance, given evidence suggesting CPT implementation in community settings is lower than those found in VA settings (Dondanville et al, 2021a ; Finley et al, 2018 ; Hundt et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therapists in community settings tend to have less experience and training in EBPs for PTSD (Finley et al, 2019 ), making it likely that implementation rates of CPT are even lower in the community than in institutional settings (Hundt et al, 2018 ). Utilization of EBPs in community settings may remain low even after therapists have received training and consultation (Dondanville et al, 2021a ; Finley et al, 2018 ). A recent survey study examined initiation rates of EBPs in community settings serving veterans following a training program for CPT and PE.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Prior research has indicated penetration is often low, even in specially trained EBP providers. For instance, work regarding EBPs for posttraumatic stress disorder (PTSD) both within the Veterans Health Administration (VHA; Finley et al, 2015), and among community providers (Dondanville et al, 2018) demonstrated therapists often fail to provide or offer EBPs to patients. Importantly for the present study, attempting to offer or initiate a given EBP to a patient is a prerequisite for the patient to receive the EBP; therefore, the percentage of patients with whom the EBP is attempted is an important measure of penetration.…”
mentioning
confidence: 99%